Business Analytics Architecture Stack to Modern Business Organizations - Palanivel, K; Manikandan, J (International Journal of Computer Sciences and Engineering, 2019)
Business Analytics is a set of techniques and processes that can be used to analyze data to improve business performance through fact-based decision-making. Business analytical applications are designed to retrieve, analyze, transform and report data for business intelligence. These business analytics applications give the organization a complete overview of the company to provide key insights and understanding of the business. So smarter decisions may be made regarding business operations, customer conversions and more. A business analytics architecture is used to build business analytical applications for reporting and data analytics. The existing business analytics architecture is designed with Data Warehouse and the data flow among various business components is unidirectional. Today, Data Lake offers an optimal foundation for modern business analytics. In the literature survey, no business analytics architecture is available with Data Lake solutions. Hence, it is proposed to design a business analytics architecture with Data Lake to meet the needs of modern business organizations. The proposed business analytics architecture supports all standardized business analytic reports with Big Data analysis. The proposed business analytics architecture provides many advantages when it comes to scalability, speed, data quality, and flexibility.